ANALISIS PENETAPAN NOMOR 53/PDT.P/2023/PN JKT.SEL MENGENAI PERMOHONAN PENCATATAN PERKAWINAN BEDA AGAMA YANG DIKABULKAN OLEH PENGADILAN NEGERI JAKARTA SELATAN: Analysis Determination Number 53/Pdt.P/2023/PN Jkt.Sel regarding the application for registration interfaith marriages granted the South Jakarta District Court - Rizky Adytiya Pratama; Muriani; -Rizky Adytiya Pratama (Reformasi Hukum Trisakti, 2024)
Interfaith marriage is a marriage in which a person with different religious beliefs and  still respective to their religions. Formulation of the problem in this study is whether the South Jakarta District Court has the authority to examine and determine applications for registration of marriages of different religions and whether the South Jakarta District Court judge used the legal considerations used in Decision Number 53/Pdt.P/2023/PN Jkt.Sel in accordance with Law Number 1 of 1974 and the Complication of Islamic Law in granting applications for registration of marriages of different religions. The research method uses normative legal research, is analytical descriptive and data collection uses library research and deductive methods of drawing conclusions. Results of the research and discussion of the South Jakarta District Court Judges are indeed authorized to determine interfaith marriages, but even though they are authorized, the South Jakarta District Court Judges should not grant the application. Conclusion is that the South Jakarta District Court Judge uses legal considerations that are contrary to Law Number 1 of 1974 concerning Marriage, the Complication of Islamic Law and religious provisions in Indonesia and also the lack of legal considerations of judges or Onvoldoende gemotiveerd in granting applications for interfaith marriages